Optimal Maturity Structure with Multiple Debt Claims - Houston, Joel F.; Venkataraman, S. (Journal of Financial and Quantitative Analysis, 1994)
This paper provides an explanation for why firms may choose to simultaneously issue multiple debt claims with varying maturities. The optimal mix of short- and long-term debt allows the firm to precommit to a more efficient liquidation policy. Even in risk-neutral settings, the optimal mix hinges critically on the mean and the variability of the firm's liquidation value. Determining the optimal mix of debt is more complex than just weighing the costs of issuing short- or long-term debt exclusively. The implications of alternate priority structures, informational settings, interest rate uncertainty, and maturity matching strategies are also considered.